Linear quadratic regulator design via metaheuristics applied to the damping of low-frequency oscillations in power systems - Carvalho, Luis; Neto, Jozias R.L.; Rezende, Jefferson C.; Costa, Marcus V. S.; Fortes, Elenilson V.; Macedo, Leonardo H. [UNESP] (Elsevier, 2023)
This paper proposes the application of control by state feedback using the linear quadratic regulator (LQR) optimized by metaheuristics to damp low-frequency electromechanical oscillations in electrical power systems. The current sensitivity model was used to represent the single machine infinite bus (SMIB) system in the time domain. The weighting matrices of the LQR were adjusted using four different algorithms: (i) the genetic algorithm, (ii) the differential evolution algorithm, (iii) the particle swarm optimization algorithm, and (iv) the gray wolf optimization (GWO) algorithm. In the cases considered, disturbances were applied to the electrical power system and, then, performances comparisons associated with each metaheuristic were statistically analyzed, in which the number of iterations, error, and time to achieve convergence of each algorithm were compared. From the results, it was possible to conclude that the algorithms were efficient in adjusting the weighting matrices of the LQR, providing additional damping to the poles of interest of the system. It was also possible to conclude that the GWO algorithm presented the best performance, accrediting it as a powerful tool in the study of small-signal stability for the analyzed case.
Keywords: Current sensitivity model; Electric power systems; Linear quadratic regulator; Metaheuristics; Small-signal stability